2021
DOI: 10.2174/1389201021999201110204735
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng Saponins Attenuate Neuroinflammation through TXNIP-Mediated NLRP3 Inflammasome Activation in Aging Rats

Abstract: Introduction:: Microglia-mediated inflammatory responses play a crucial role in aging-related neurodegenerative diseases. The TXNIP/NLRP3 pathway is a key pathway leading to microglial activation. Panax notoginseng saponins (PNS) have been widely used for the treatment of stroke in China. Objective:: This study evaluates the anti-neuroinflammatory effect of PNS and investigates the mechanism via TXNIPmediated NLRP3 inflammasome activation in aging rats. Materials and Methods:: Eighteen-month-old Sprague-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“… 1 , 26 As is well known, neuroinflammation is strongly associated with activation of the NLRP3 inflammasome. 7 , 11 , 13 , 27 The classical pyroptosis pathway involves formation of the NLRP3 inflammasome, which is comprised of NLRP3, ASC, and pro-caspase-1. After activation, NLRP3 recruits ASC protein, which then recruits the pro-caspase-1 and promotes cleavage to caspase-1, resulting in production and secretion of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 26 As is well known, neuroinflammation is strongly associated with activation of the NLRP3 inflammasome. 7 , 11 , 13 , 27 The classical pyroptosis pathway involves formation of the NLRP3 inflammasome, which is comprised of NLRP3, ASC, and pro-caspase-1. After activation, NLRP3 recruits ASC protein, which then recruits the pro-caspase-1 and promotes cleavage to caspase-1, resulting in production and secretion of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Chikusetsu saponin IVa, a major active triterpenoid saponin in Panax japonicus , inhibited NLRP3 inflammasome activation, hence ameliorating obesity and neuroinflammation in macrophages, adipocytes, primary neurons, and postoperative cognitive dysfunction rats [ 75 , 76 ]. PF11, pseudoginsenoside, in Panax quinquefolius and saponins in Panax notoginseng inhibited NLRP3 inflammasome initiation, attenuating age-related neuroinflammation in macrophages and neurons [ 77 , 78 ].…”
Section: Inhibitory Role Of Ginseng In Inflammasome Activationmentioning
confidence: 99%
“…Later, Zhou et al [ 67 ] found that aging is associated with elevated microglial activation and neuroinflammation along with increased TXNIP/NLRP3 expression in aged rat (24 mo) in comparison with young rats (12 mo). Further, modulating TXNIP-NLRP3 activation with a traditional anti-inflammatory Chinese medicine attenuated age-associated neurodegeneration in aging rats[ 93 ]. Consistently, we recently identified aged-dependent activation of TXNIP-NLRP3 inflammasome in the cortex and hippocampus of brain in both male and female mice[ 94 ].…”
Section: Txnip-nlrp3 Inflammasome Activation In Neurodegenerationmentioning
confidence: 99%